2018
DOI: 10.1016/j.bbalip.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and microRNA analyses of gene networks regulated by eicosapentaenoic acid in brown adipose tissue of diet-induced obese mice

Abstract: Brown adipose tissue (BAT) dissipates chemical energy as heat via thermogenesis and protects against obesity by increasing energy expenditure. However, regulation of BAT by dietary factors remains largely unexplored at the mechanistic level. We investigated the effect of eicosapentaenoic acid (EPA) on BAT metabolism. Male C57BL/6J (B6) mice fed either a high-fat diet (HF, 45% kcal fat) or HF diet supplemented with EPA (HF-EPA, 6.75% kcal EPA) were used for 11 weeks. RNA sequencing (RNA-Seq) and microRNA (miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 71 publications
(96 reference statements)
2
18
0
Order By: Relevance
“…EPA binding and activation of GPR120 promotes several effects, including (i) the interaction with PPAR-γ that favors the differentiation of pre-adipocytes into white adipocytes [ 40 ], (ii) the binding to β-arrestin2 and their interaction with transforming growth factor-β-activated kinase binding protein 1 (TAB1) that blocks NF-κΒ and c Jun N-terminal kinase (JNK) functioning, with inhibition of the low-grade inflammation due to TNF-α and IL-6 production by ATMs triggered by obesity [ 41 ] and (iii) the release of fibroblast growth factor 21 (FGF21), resulting in the promotion of brown adipose tissue (BAT) activity and WAT browning [ 42 ], with stimulation of mitochondrial energy metabolism depressed by HFD. It is important to note that EPA supplementation in HFD-fed mice upregulates the expression of PPAR-α and the micro-RNAs miR-455 and miR-129-5p in BAT [ 43 ]. These mediators enhance the expression of thermogenic markers that stimulate mitochondrial FAO and energy expenditure, pointing to BAT as a crucial anti-obesity target [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPA binding and activation of GPR120 promotes several effects, including (i) the interaction with PPAR-γ that favors the differentiation of pre-adipocytes into white adipocytes [ 40 ], (ii) the binding to β-arrestin2 and their interaction with transforming growth factor-β-activated kinase binding protein 1 (TAB1) that blocks NF-κΒ and c Jun N-terminal kinase (JNK) functioning, with inhibition of the low-grade inflammation due to TNF-α and IL-6 production by ATMs triggered by obesity [ 41 ] and (iii) the release of fibroblast growth factor 21 (FGF21), resulting in the promotion of brown adipose tissue (BAT) activity and WAT browning [ 42 ], with stimulation of mitochondrial energy metabolism depressed by HFD. It is important to note that EPA supplementation in HFD-fed mice upregulates the expression of PPAR-α and the micro-RNAs miR-455 and miR-129-5p in BAT [ 43 ]. These mediators enhance the expression of thermogenic markers that stimulate mitochondrial FAO and energy expenditure, pointing to BAT as a crucial anti-obesity target [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that EPA supplementation in HFD-fed mice upregulates the expression of PPAR-α and the micro-RNAs miR-455 and miR-129-5p in BAT [ 43 ]. These mediators enhance the expression of thermogenic markers that stimulate mitochondrial FAO and energy expenditure, pointing to BAT as a crucial anti-obesity target [ 43 ]. This contention is further supported by data showing that HT prevents visceral adipogenesis and decreased metabolic activity in BAT and WAT, induced by the exposure to fine particulate matter in mice [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-129: MiR-129 is a positive regulator of BAT function which is involved in thermogenesis and energy expenditure [ 92 , 112 ]. This miRNA targets both Igf2 (insulin like growth factor 2) and Egr1 (Early growth factor response 1), with both these factors being UCP1 inhibitors [ 92 , 112 ]. A recent study by Fu et al showed that MiR-129 also directly targets ATG7 (Autophagy-related gene 7), which is an essential autophagy gene [ 89 ].…”
Section: Micrornas In Batmentioning
confidence: 99%
“…Indeed, this study showed that MiR-455 downregulates Ucp1 expression through interaction with a target site of MiR-455 in the coding region of mouse Ucp1 [ 91 ]. Another study by Pahlwani et al showed MiR-455 thermogenic effects by targeting key brown adipogenic signaling molecules including Hif1an , Pparg , and type III transforming growth factor-β receptor ( Tgfbr3 ) [ 92 ]. Notably, Hif1an appears to serve as an intermediate target between MiR-455 and Notch1, with MiR-455 reducing Notch1 expression which, in turn, promotes WAT browning [ 92 ].…”
Section: Micrornas Regulating Bat and Britementioning
confidence: 99%
“…The supplementation level of EPA was based on previous studies . Here, 44 g EPA‐ethyl ester (EPA‐EE, molecular weight 330.5, 90% purity) was used to replace lard in the HFD (60% kcal, 30.1 % w/w lard content).…”
Section: Methodsmentioning
confidence: 99%